(untitled) (Computer systems and information technologies, 2025)
The paper presents a method and a software-hardware tool for an access control system based on biometric data. The method involves the collection, processing, and verification of biometric features such as fingerprints, facial recognition, or iris scans to authenticate individuals. The system ensures secure access while minimizing the risks associated with traditional password-based security systems. The software-hardware tool integrates biometric sensors, data storage, and authentication algorithms to provide an efficient and secure means of controlling access to protected areas or resources. This approach aims to enhance security, streamline user access, and reduce the likelihood of unauthorized access or identity theft.